THE INFLUENCE OF LEADERSHIP STYLE, COMMUNICATION, AND MOTIVATION ON TEAM WORK EFFECTIVENESS THROUGH JOB SATISFACTION AND TEAM COMMITMENT AS INTERVENING VARIABLES (A CASE STUDY OF TJIWI KIMIA EMPLOYEES' COOPERATIVE) - Dara Anindya Putri Umagapi; Arief Noviarakhman Zagladi (CV. Radja Publika, 2026)
This study aims to explore the influence of leadership style, communication, and motivation on team effectiveness, with job satisfaction and team commitment considered as mediating variables in the Tjiwi Kimia Employees’ Cooperative. This research employs a quantitative approach using a survey method involving a sample of 35 respondents. The Partial Least Squares Structural Equation Modeling (PLS-SEM) technique is applied to analyze the relationships between the studied variables. The findings indicate that leadership style, communication, and motivation significantly affect team effectiveness, both directly and indirectly through job satisfaction and team commitment. Participative leadership, effective and open communication, and high motivation play crucial roles in enhancing team members’ satisfaction and commitment, ultimately leading to improved team effectiveness overall. Practically, the study recommends that cooperative management adopt participative leadership strategies, enhance communication, and provide motivation to boost team engagement. However, the scope of this research is limited to a single cooperative, and further studies are needed to generalize these findings to other organizations. Future research is expected to involve a more diverse range of organizations and employ qualitative approaches to gain deeper insights.